MODEL PENYUSUNAN HARGA PERKIRAAN SENDIRI (HPS) PENGADAAN BARANG/JASA PEMERINTAH DI PROVINSI BALI - I Gusti Agung Adnyana Putera; Ida Bagus Putu Adnyana; I Gede Bambang Wahyudi (JURNAL SPEKTRAN, 2019)
PREPARATION PRICING MODEL OF OWN ESTIMATION IN PROCUREMENT OF GOODS AND SERVICES IN PROVINCE GOVERNMENT BALIABSTRACT Own Estimate (OE) is the price of goods and or services calculated and determined by expertise and based on reliable data. Government, especially Bali Province in the procurement of goods / services in the planning process must set the value of HPS. This study aims to find out how the model calculates HPS on the procurement of goods / services government, especially in Bali Province. HPS preparation model in this study is reviewed on the object of procurement of Goods, Construction and Consulting Services. Data collection was conducted through survey by spreading questionnaires to government agencies that were deemed to be representative to answer the questionnaire in order to describe the model of HPS preparation. The questionnaire was prepared based on Presidential Decree 54 of 2010 and its amendment and Presidential Regulation No. 16 of 2018 concerning Government Procurement of Goods / Services especially regarding Own Estimate (OE) and interview to government officials related to the preparation of HPS. The research instrument uses Guttman scale for clear and consistent answers which then tested the validity and reliability using SPSS 20 program. The result of the Modus analysis on each procurement object variable shows the value that can be used for the HPS preparation model. The procurement model of procurement HPS through E-Purchasing generally shows Price HPS = lowest justification price (X1) + Postal fee (X2) + installation fee (X3) +risk of price increase (X4), procurement through Non E-Purchasing shows Price HPS = lowest justification price (X1) + Postal fee (X2) + installation fee (X3) + benefit provider (X4) + risk of price increase (X5), Procurement Construction Price HPS = lowest justification price (X1) + Provider profit (X2) + risk of price increase (X3), and Consultancy Service Provision Price HPS = Average justification price (X1) + general cost (X2) + social cost (X3) + company profit (X4) + risk of price increase (X5).